ANALISIS PEMASARAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) DI KOTA PEKANBARU - Wan Azmiliana; Ermi Tety; Yusmini Yusmini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research are: (1) to analyze the marketing functions; and (2) to analyze the marketing channels. The research method used survey method with 10 white oyster mushroom farmers, 2 brokers, and 31 retailers. The result showed that marketing functions undertaken by institutions who involved in the marketing of white oyster mushroom include farmers, brokers, and retailers such as exchange function, physical function, and function facilities. Marketing channels of white oyster mushroom in Pekanbaru city consists of three channels, where Channel I farmer selling white oyster mushroom to consumer directly, Channel II farmer selling white oyster mushroom to retailer, and then retailer selling mushroom to consumer, and Channel III farmer selling white oyster mushroom to broker, then broker selling mushroom to retailer, and finally retailer selling mushroom to consumer. Keywords: White oyster mushroom, Marketing functions, Marketing channel